Acute peritoneal dialysis in neonatal intensive care unit: An 8-year experience of a referral hospital - Kara, Aslihan; Gurgoze, Metin Kaya; Aydin, Mustafa; Taskin, Erdal; Bakal, Unal; Orman, Aysen (Elsevier Taiwan, 2018)
Background: The aim of present study was to evaluate the indications, complications and outcomes of acute peritoneal dialysis (APD) in neonates at a referral university hospital during the previous 8 years. Methods: This retrospective analysis included a total of 52 newborn infants who underwent APD in a neonatal intensive care unit between January 2008 and March 2016. Demographic, clinical, laboratory and microbiological data were extracted from patient's medical files. Results: The primary causes for requiring APD were acute tubular necrosis (n = 36, 69.2%), inborn error of metabolism (n = 10, 19.2%), congenital nephrotic syndrome (n = 2, 3.9%), bilateral polycystic kidney (n = 2, 3.9%), renal agenesis (n = 1, 1.9%), and obstructive uropathy (n = 1, 1.9%). The mean duration of APD was 8.7 I 15.87 days (range: 1-90 days). Procedural complications were mainly hyperglycemia (n = 16, 47.1%), dialysate leakage (n = 7, 20.6%), peritonitis (n = 3, 8.8%), catheter obstruction (n = 3, 8.8%), bleeding at the time of catheter insertion (n = 2, 5.9%), catheter exit site infection (n = 2, 5.9%), and bowel perforation (n = 1 2.9%). There were 40 deaths (76.9%), mainly due to underlying causes. Ten of the 12 survivors showed full renal recovery, but mild chronic renal failure (n = 1) and proteinuria with hypertension were seen (n = 1) in each of remaining patients. Conclusion: Peritoneal dialysis is an effective route of renal replacement therapy in the neonatal period for management of metabolic disturbances as well as renal failure. Although major complications of the procedure are uncommon, these patients still have a high mortality rate due to serious nature of the underlying primary causes.Copyright (C) 2017, Taiwan Pediatric Association. Published by Elsevier Taiwan LLC.
Keywords: acute peritoneal dialysis; complication; mortality; neonatal intensive care unit; newborn